2006
DOI: 10.1007/s11157-006-0010-3
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of the food sufficiency through salt tolerant crops

Abstract: This work is focused on deserts, as extreme environments, because the year 2006 has been declared Year of Deserts and Desertification by the United Nations (IYDD Program 2006). The loss of vital resources such as fresh water and soil, and the depletion of biodiversity are emerging hazards, able to transform beneficial situations into extreme environments. Desertification is generated by land degradation: the loss of biological productivity is caused by nature or by human-induced factors and climate change. Nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 16 publications
0
22
0
2
Order By: Relevance
“…This pressure is particularly high in developing countries". Agriculture is the first human activity and represents the major use of land across the world [5]. Agriculture can be defined as an "artificial management to enhance the food value of cultivated land" and represents "the major land use across the globe" [6].…”
Section: Human Population Growth and Agriculture Challenges In The 21mentioning
confidence: 99%
See 2 more Smart Citations
“…This pressure is particularly high in developing countries". Agriculture is the first human activity and represents the major use of land across the world [5]. Agriculture can be defined as an "artificial management to enhance the food value of cultivated land" and represents "the major land use across the globe" [6].…”
Section: Human Population Growth and Agriculture Challenges In The 21mentioning
confidence: 99%
“…However, in 2004, FAO also highlighted that despite in most places these hunger issues translate a real lack of food and deficient agricultural techniques. This problem is however the convergence of more complex problems [5]. This is evident by the statistical data pointing to approximately 9 million hungry people in industrialized countries where in theory there is no lack of food [10].…”
Section: Human Population Growth and Agriculture Challenges In The 21mentioning
confidence: 99%
See 1 more Smart Citation
“…Selamat and Ismail (2008) reported that fifty per cent yield is being lost of the salt-sensitive rice genotypes due to salinity. Therefore, production of rice under saline condition is under pressure because salinity may cause plant demise, growth and development (Galvani, 2007;Roychoudhury et al, 2008) …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, methods or practices that increase water use efficiency, soil productivity and reduce the excessive amount of water applied are of importance for conserving water. The effect of the quality of irrigation water on soil properties has been discussed by many researchers [3][4][5][6][7][8][9][10][11][12][13]. Ragab [14] found that soil electrical conductivity (EC s ) values increased with increasing salinity of irrigation water and decreased soil moisture depletion in calcareous soil.…”
Section: Introductionmentioning
confidence: 99%